What the living carry (London : MACK, 2017)
What the Living Carry unveils a small town named Hoy's Fork, situated in the American South. Drawing on memories of the rural setting in which he grew up, Virginian photographer Morgan Ashcom brings together photographs, type-written letters and a hand-drawn map to build a fictional narrative of a foreboding place. Leading us on a trail through the town and its surrounding forest, Ashcom presents scenes that point to a mysterious history, and people whose familial connections remain unknown: a forlorn old man, with champagne to hand, reclines on the corroding steps of a once grand home; a bloodied mattress is carried through an overgrown field; a solitary child burrows into a meadow, while on the streets, a man dutifully cleans a white picket fence -- a vision that belies a local mural of a distant, ancient land. Interspersing this fragmented narrative is a set of texts -- four letters responding to 'Morgan's' request for DNA analysis -- written by 'Eugene' of the 'Center for Epigenetics and Wellness of the Spirit'. If What the Living Carry provides a set of clues to unravel the enigma behind this strange world, it is through a visual record that is simultaneously autobiographical and imagined, and inclined to elude.
Cover title.
Inside the text contains 4 type-written letters (totalling 7 pages) and a hand-drawn map.
boek
Keywords: Ashcom, Morgan